The Nationality Of Commercial Control Of World Minerals (faef746f-3f58-4223-a339-2ff36af99732) - William Rawles (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1933)
THIS report is the first of a series planned by The Mineral Inquiry, organized by the American Institute of Mining and Metallurgical Engineers to make factual studies of the world's mineral resources in their political and international relations. The efforts of The Inquiry are directed toward filling certain notable gaps in available information, without duplication of many other investigations touching this field which are being conducted by other organizations, public and private. Much of its work is indirect-suggesting topics for study by other individuals and organizations and aiding in their planning and correlation. The present report is designed to show the nationality of the commercial control of mineral resources, in addition to the geographic distribution of production by nation-in other words, the overlapping of political and commercial control. Detailed accuracy cannot be claimed for the figures presented. For some companies division of ownership by nationality has been very difficult to ascertain, as many companies are reluctant to dis-close the extent of their holdings in other corporations, and the impossi-bility of tracing all stock ownership is obvious. Also there are frequent changes in the distribution of. stock control. The percentages given rep-resent only the participation that has been identified definitely, even though it is known in some cases with fair certainty that larger interests exist, as, for instance, American participation in foreign chromite companies. In bringing together these figures we have had the cordial co-operation of the United States Bureau of Mines, the United States Geologi-cal Survey, the Mineral Division of the Bureau of Foreign and Domestic Commerce, the Brookings Institution, and of many specialists connected with the mineral industries covered. The report does not cover the entire list of minerals. Coal, although it is one of the most important minerals, was omitted because , not more than one or two per cent of the world's production comes from mines that are owned by companies foreign to the countries where the coal is produced. Others, such as gold, are omitted because sufficient data have not yet been accumulated. It is hoped that some of these may be covered in subsequent reports. It is not our purpose here to discuss the significance of the figures sub-mitted, but only to point out the general nature of the problems on which they have a bearing.